1991
DOI: 10.1152/ajpendo.1991.260.6.e883
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate supplementation, glycogen depletion, and amino acid metabolism during exercise

Abstract: Eight highly trained cyclists were studied during exercise after glycogen depletion (test A) and during carbohydrate (CHO) loading (test B). In test B subjects were able to complete 2 h of exercise at 70-75% maximal workload (Wmax), whereas the initial intensity of 70% Wmax had to be reduced to 50% in test A. Plasma ammonia increased more rapidly, and plasma alanine, glutamate, and glutamine were lower in test A. Exercise caused a 3.6-fold increase in the proportion of active branched-chain 2-oxoacid dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
1
13

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 22 publications
5
136
1
13
Order By: Relevance
“…However, fat oxidation may not be sufficient to maintain the power output required during the cycling time-to-exhaustion test. In fact, a number of studies have reported that exogenous carbohydrate supplementation, especially when muscle glyco-Carbohydrate availability and time to exhaustion www.bjournal.com.br gen concentrations are low, can maintain blood glucose and total carbohydrate oxidation and delay the onset of fatigue (4)(5)(6)(7)(8)(9). Therefore, while carbohydrate-loading diets are associated with improved endurance capacity, ascribed mainly to maintenance of a high rate of carbohydrate oxidation throughout exercise, low carbohydrate diets have been shown to impair endurance exercise capacity, which has been ascribed to anticipated reduction of endogenous carbohydrate availability and to a decreased rate of carbohydrate oxidation (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, fat oxidation may not be sufficient to maintain the power output required during the cycling time-to-exhaustion test. In fact, a number of studies have reported that exogenous carbohydrate supplementation, especially when muscle glyco-Carbohydrate availability and time to exhaustion www.bjournal.com.br gen concentrations are low, can maintain blood glucose and total carbohydrate oxidation and delay the onset of fatigue (4)(5)(6)(7)(8)(9). Therefore, while carbohydrate-loading diets are associated with improved endurance capacity, ascribed mainly to maintenance of a high rate of carbohydrate oxidation throughout exercise, low carbohydrate diets have been shown to impair endurance exercise capacity, which has been ascribed to anticipated reduction of endogenous carbohydrate availability and to a decreased rate of carbohydrate oxidation (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that exercise in the fasted state, compared with exercise in the fed state, generates a number of specific metabolic responses, most typically enhanced contribution of fat oxidation in energy provision, but also higher rate of muscle protein degradation (Gibala 2007;Koopman et al 2004). Furthermore, net muscle protein breakdown is markedly enhanced during exercise when muscle glycogen stores are depleted (Wagenmakers et al 1991;Jackman et al 1997). In this regard, we have previously shown that net glycogen degradation is enhanced during exercise in the fasted state (De Bock et al 2007a), which conceivably could result in premature glycogen depletion.…”
Section: Pln (mentioning
confidence: 90%
“…Thus, if no training adaptations were present one would rather expect a blunted eEF2 response after an exercise bout with high carbohydrate availability following a period of consistent fasted exercise. Second, given the greater rate of muscle protein degradation during exercise in the carbohydrate-depleted state than during exercise with high carbohydrate availability (Gibala 2007;Wagenmakers et al 1991;Jackman et al 1997;Koopman et al 2004), rapid re-activation of eEF2 conceivably could contribute to facilitating post exercise protein repair during a period of consistently repeated exercise in the fasted state. Such mechanism is probably redundant during consistent exercise training with ample carbohydrate intake.…”
Section: Pln (mentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased glycogen stores are consistently demonstrated in subjects consuming low carbohydrate diets (Coggan & Mendenhall, 1992). Several investigators reported indices of accelerated protein breakdown in response to endurance exercise in athletes who were glycogen depleted vs glycogen repleted (Bazarre et al, 1992;Lemon and Mullin 1980;Wagenmakers et al, 1991). If the endurance athlete continues training in a chronic glycogen-depleted state, negative changes in body composition could result over time.…”
Section: Long-term Consequences Of High-fat Dietmentioning
confidence: 99%